41.4.





: -X = NOT(X) + 1 -X = NOT(X - 1) NOT(X) = -X - 1 - NOT(X) = X + 1 NOT(-X) = X - 1 X + Y = X - NOT(Y) - 1 = (X ^ Y) + 2 (X & Y) = (X | Y) + (X & Y) = 2 (X | Y) - (X ^ Y) X - Y = X + NOT(Y) + 1 = (X ^ Y) - 2(NOT(X) & Y) = (X & NOT(Y)) - (NOT(X) & Y) = 2 (X & NOT(Y)) - (X ^ Y) X ^ Y = (X | Y) - (X & Y) X & NOT(Y) = (X | Y) - Y = X - (X & Y) NOT(X - y) = Y - X - 1 = NOT(X) + Y X EQV Y = (X & Y) - (X | Y) - 1 = (X & Y) + NOT(X | Y) X | Y = (X & NOT(Y)) + Y X & Y = (NOT(X) | Y) - NOT(X)

Index Prev Next